Microstrain Partitioning, TRIP Kinetics and Damage Evolution in Third Generation Dual Phase and TRIP-Assisted Advanced High Strength Steels - Pelligra, Concetta (My University, 2024)
Lightweighting demands have been achieved by third generation (3G) Advanced High Strength Steels (AHSSs) by a means of increased strength. The challenge faced in doing so, however, is in ensuring that ductility and crashworthiness is efficiently retained. Key methods in which automotive research has been invested to achieve this strength-ductility balance is by microalloying to promote grain refinement, the introduction of precipitates, and the effective use of plasticity enhancing mechanisms. Specifically, the ability to tailor the stability of retained austenite during deformation has been crucial in manipulating the strength-to-ductility ratio of 3G AHSSs using the Transformation Induced Plasticity (TRIP) effect. On the other hand, dual phase (DP) (i.e: non-TRIP-assisted steels) continue to be most significantly manufactured due to their robust thermomechanical processing but are also compromised by their poor damage tolerance. Hence, considerable reports are available regarding the damage tolerance of DP steels, but the ability for the volume expansion associated with the austenite-to-martensite transformation to suppress damage evolution and enhance a steel’s local formability has not yet been thoroughly investigated. Nonetheless, the damage processes that lead to fracture in 3G AHSSs are complex. A full understanding of the underlying phenomena requires a careful assessment of the strain partitioning amongst phases, how the microstructure evolves with strain and how damage, in the form of voids and micro-cracks, nucleates and grows. This can only be accomplished by applying a range of methodologies, including microscopic Digital Image Correlation (µDIC), X-ray Computed Microtomography (µXCT), Electron Backscattered Diffraction (EBSD) and X-ray Diffraction (XRD), all of which can be tracked as deformation proceeds. This PhD thesis uses a novel post µDIC data processing technique to prove that a reduction in strain gradient, linked to the evolution Geometrically Necessary Dislocations (GNDs), at dissimilar phase interfaces is attainable with vanadium-microalloying and with use of the TRIP effect. A local strain gradient post µDIC data processing technique was developed and first applied on 3G DP steels to show that the microcompatibility between ferrite and martensite directly at the interface is considerably improved with vanadium-microalloying. This in turn microscopically explains this DP steel’s increased local formability/damage tolerance with vanadium micro-additions. Moreover, when applying this novel µDIC technique on two other 3G experimental steels of interest, an ultrahigh strength Quench & Partition (Q&P) steel and a continuous galvanizing line (CGL)-compatible Medium-Mn (med-Mn) steel, an even slower evolution of microstrain gradients at dissimilar phase interfaces was observed. This indicates that, although vanadium-microalloying can improve the damage tolerance of a DP steel, its ability to achieve the ultrahigh strengths is a direct result of the severe inhibition of dislocation motion at dissimilar phase boundaries. Eventually, at high strains, these local strain gradients cannot be maintained and results in premature damage nucleation. By comparison, at such high strains, distinct evidence of damage nucleation was not apparent in the 3G TRIP-assisted steels which is the result of a slow strain gradient evolution delayed by the effective use of TRIP. This finding triggered a further investigation into isolating the impact the rate of TRIP exhaustion has on damage development. By intercritically annealing this prototype med-Mn steel (0.15C-5.8Mn-1.8Al-0.71Si) with a martensitic starting microstructure, within a narrow temperature interval (from 665 to 710°C), it was possible to make significant changes in the steel’s rate of TRIP exhaustion without making considerable changes to its physical microstructure. This steel exhibits the largest true strain at fracture (ɛf = 0.61), meets U.S. Department of Energy (DoE) mechanical targets (28,809 MPa%), and shows sustained monotonic work hardening when intercritically annealed at an intermediate IA temperature of 685°C for 120s. In addition, this IA condition showed optimal damage tolerance properties as an abundance of voids nucleated during its tensile deformation, but their growth was suppressed by prolonging TRIP over a large strain range. There is reason to believe that the heterogeneous distribution of austenite and Mn throughout this 685°C IA condition compared to the other two enabled its suppressed TRIP kinetics and in turn improved damage tolerance. The impact that changes in stress-state, from a stress triaxiality of 0.33-0.89, has on microstrain partitioning, TRIP kinetics and damage evolution was tested on this med-Mn at its 685°C IA condition. With the machining of notches on tensile specimens, it was seen that a high stress triaxiality (0.74-0.89) accelerated the rate of TRIP, whereas the introduction of shear, through a misaligned notched specimen design, delayed TRIP kinetics. The change in mean stress imposed by the notches was deemed to have played an active role in TRIP exhaustion during the material’s tensile deformation. A unique electropolishing micro-speckle patterning technique was applied to show that the amount of strain that can be accommodated by the steel’s the polygonal ferrite-tempered martensitic regions are considerably impacted by external modifications in stress-state. While damages studies using different such notched tensile geometries revealed that once a critical void size is reached in this med-Mn steel, coalescence proceeds at an increasing, exponential rate up to fracture. It continues to remain a challenge to quantify the effects microstrain partitioning, TRIP kinetics and damage evolution separately, opening new avenues for future experimental and modeling investigations.
Keywords: Transformation Induced Plasticity; Damage Development; Digital Image Correlation; Advanced High Strength Steels; X-ray Computed Tomography